TINDAK KOMUNIKASI PENDATANG DALAM RANGKA ADAPTASI BUDAYA - Adinda Geraldine Eulike Bertin; Rini Darmastuti (JIKE: Jurnal Ilmu Komunikasi Efek, 2018)
Satya Wacana Christian University is famously known as mini Indonesia, this is because students who pursue their education in this campus come from various regions, tribe and ethnicities in this country. On one hand this condition brings diversity that characterizes Indonesia. On the other hand, diversity requires the existence of mutual adjustment, adaptation and respect. Therefore, understanding how each ethnic group adapts becomes an urgency. In Satya Wacana Christian University, from the various tribes and ethnicities, Papuans and Malukuese ethnics are two fairly large ethnic groups that are in this university. Through a qualitative descriptive approach, this paper seeks to express acts of communication by migrants (especially Papuans and Malukuese ethnics) when adapting in cultures. The results of this research are divided into 3 phases, first phase or the first year of the informant or students from ethnic outsiders still huddle or socialize with his group, the second stage or second year they already want to open up more to blend in with other groups, and the third stage is a stage where they're really able to master themselves and adapt to new environments. Keywords: Intercultural Communication, Migrant Communication Actions, Cultural Adaptation, Satya Wacana Christian University.